2016
DOI: 10.1007/s12079-016-0371-5
|View full text |Cite
|
Sign up to set email alerts
|

Periostin is required for matricellular localization of CCN3 in periodontal ligament of mice

Abstract: CCN3 is a matricellular protein that belongs to the CCN family. CCN3 consists of 4 domains: insulin-like growth factor-binding protein-like domain (IGFBP), von Willebrand type C-like domain (VWC), thrombospondin type 1-like domain (TSP1), and the C-terminal domain (CT) having a cysteine knot motif. Periostin is a secretory protein that binds to extracellular matrix proteins such as fibronectin and collagen. In this study, we found that CCN3 interacted with periostin. Immunoprecipitation analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
16
1
Order By: Relevance
“…Thus, we propose that ECM proteins, such as fibronectin and collagen, might dock to the concave side of the dimer where the EMI domain inhabits. Meanwhile, the four Fas1 domains of periostin may bind to tenascin , BMP‐1 , CCN3 , and integrin . Noteworthy to mention, monoclonal antibodies recognizing a region covering residues 136–151 in the Fas1 domain may inhibit integrin‐mediated cell migration .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose that ECM proteins, such as fibronectin and collagen, might dock to the concave side of the dimer where the EMI domain inhabits. Meanwhile, the four Fas1 domains of periostin may bind to tenascin , BMP‐1 , CCN3 , and integrin . Noteworthy to mention, monoclonal antibodies recognizing a region covering residues 136–151 in the Fas1 domain may inhibit integrin‐mediated cell migration .…”
Section: Discussionmentioning
confidence: 99%
“…This matched case-control study was conducted on 53 patients with chronic periodontitis and 53 healthy peers. Three periodontal parameters were evaluated and recorded for each patient: Bleeding on Probing (BOP) [3], Clinical Attachment Level (CAL) [13], and Probing Pocket Depth (PPD). All evaluations were performed by a periodontist.…”
Section: Methodsmentioning
confidence: 99%
“…It is characterized by loss of gingival adhesions and, in more advanced stages of the disease, alveolar bone resorption [1]. Perios-P tin is a matriarchal protein secreted by periodontal ligament fibroblasts [3]. The role of periostin in tooth development is very important [4].…”
Section: Introductionmentioning
confidence: 99%
“…Periostin is reported to bind to several extracellular matrix (ECM) molecules and growth factors such as type I collagen and Notch1 8 , 9 . It has been reported that Periostin directly interacts with Fibronectin 10 through its EMI domain, while Tenascin-C 7 , CCN3 11 and BMP1 12 through Fas I domain. These findings suggest that Periostin is a multi-functional protein possibly through orchestrating these binding proteins inside and outside of the cell 13 .…”
Section: Introductionmentioning
confidence: 99%
“…while Tenascin-C 7 , CCN3 11 and BMP1 12 through Fas I domain. These findings suggest that Periostin is a multifunctional protein possibly through orchestrating these binding proteins inside and outside of the cell 13 .…”
mentioning
confidence: 99%